Research on automatic detection system of encoder accuracy based on PID algorithm. Issue 1 (February 2021) - Hou, Han; Cao, Guohua; Ding, Hongchang; Zhao, Changfu; Wang, Aijia
Abstract: After the encoder completes the installation and adjustment work, its accuracy needs to be checked again to confirm whether it meets the acceptance conditions. This process is usually manually operated by inspectors, and the inspection efficiency is low and there are certain manual errors. In order to improve this situation, an encoder automatic precision inspection system based on PID algorithm is designed. In this article, the working principle and structure of the detection platform are introduced in the first part, and then designs the corresponding detection software and operation interface according to its working characteristics. Finally, the platform was tested in combination with the actual detection products, and the encoder signal acquisition results were given, which further verified the accuracy and reliability of the detection device. The results showed that the accuracy detection platform can accurately and conveniently realize the error detection of the encoder's function, and to a certain extent overcome the detection error caused by the drift of the photoelectric autocollimator during the detection process.